MENGUKUR HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) - Ivanatul Nurizza; Wuli Oktiningrum (Program Studi Pendidikan Matematika, 2020)
Implementation of the teaching and learning process in general still use conventional learning models so as to result in low mathematics learning outcomes of students, especially in the surrounding material and flat building area. This study aimed to measure the differences in learning outcomes of class IV students through STAD (Student Teams Achievement Division) learning model and conventional learning. This study used quasi-experimental quantitative research design by looking at the differences in mathematical value results in pre-test and post-test between control class and experimental class. Based on the data analysis, the results of the study showed that there were differences in the learning outcomes of mathematics students of class IV who use the learning model Student Teams Achievement Division (STAD) and conventional learning. This was evidenced by the average value of the control class which increased by 9.88% from 54.36 to 64.24 while the average value of the class in the experimental class reached 24.92% from 55.80 to 80.72.